2008
DOI: 10.1021/la7027324
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Structural Effects on the Liquid-Crystalline Properties of Ionic Perylenebis(dicarboximide)s Using UV−Vis Spectroscopy, Polarized Light Microscopy, and NMR Spectroscopy

Abstract: Ionic perylenebis(dicarboximide)s 1-5 were synthesized. The aggregation and liquid-crystalline properties of these compounds in aqueous solutions were investigated. In the concentration range of approximately 5 x 10-7-5 x 10-4 M, the structures of the ammonium side chains and counterions did not have a significant effect on the electronic transition properties and H-aggregate formation of these compounds. However, the liquid-crystalline phase properties varied with the structure of the side chains and the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Self-Aggregation of PDI. The phase behavior of PDI was already reported by Tam-Chang et al 26 PDI forms a chromonicnematic (N) phase from a concentration of about 6 wt %. At higher concentrations, a hexagonal (M) phase was detected.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Self-Aggregation of PDI. The phase behavior of PDI was already reported by Tam-Chang et al 26 PDI forms a chromonicnematic (N) phase from a concentration of about 6 wt %. At higher concentrations, a hexagonal (M) phase was detected.…”
Section: Resultsmentioning
confidence: 52%
“…26 The molecular structure of PDI is shown in Figure.1. Tetraethyl orthosilicate (TEOS) was purchased from Sigma-Aldrich.…”
Section: Introductionmentioning
confidence: 99%
“…464−468 Their detailed studies have shown that the self-assembly properties of these PBIs in water at lower concentrations (5 × 10 −7 to 5 × 10 −4 M) are independent of their ammonium substituents and counterions because all of these PBIs formed H-type aggregates with similar electronic transitions in absorption spectra, while lyotropic LC properties varied with the structural changes in imide substituents and counterions as well. 467 Cationic PBIs 6-7a,c with chloride counterions form nematic phases from the isotropic phase, while PBIs 6-7b,d with tosylate counterions form ribbonlike optical textures. When ethylene unit in ammonium side chains of PBIs 6-7a,c is replaced by a bulky group as in PBI 6-7e, the nematic phase of the latter is formed at higher concentration than those for 6-7a,c at the same temperature ( Figure 63).…”
Section: Liquid-crystalline Ionic Pbismentioning
confidence: 99%
“…S1) and found in the refs 36, 37, 38. The acrylation reaction between anhydride and alcohol in the presence of 4-dimethylaminopyridine (DMAP) results in the targeted PBRM molecule.…”
Section: Resultsmentioning
confidence: 85%
“…To realize this concept, a perylene-based reactive mesogenic molecule (abbreviated as PBRM) containing diacrylate functional groups at the ends of the molecule is strategically designed and synthesized363738. The PBRM MOTF is fabricated by the simple shear coating and photopolymerization process.…”
mentioning
confidence: 99%